PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI: indonesia - Permatasari, Felia; Widianingsih, Luky Patricia (Media Akuntansi dan Perpajakan Indonesia, 2020)
The purpose of this studies is to know how the influence of CSR disclosure on financial performance with GCG as a moderating variable. CSR disclosure is measured using CSRD Index based on GRI G4. The dependent variable of this study is financial performance which is proxied by return on assets and return on equity. The GCG moderation variable is proxied by institutional ownership, the size of the board of commissioners and the independent board of commissioners. The sample used in this study is a SOE’s company non-financial listed on the Indonesia Stock Exchange in the period 2014–2018. The results of this studies found that CSR disclosure has a positive effect on financial performance (ROA) and CSR disclosure has no effect on financial performance (ROE). GCG variables which are proxied by institutional ownership is not able to moderate the effect of CSR on financial performance (ROA and ROE), the size of the board of commissioners able to strengthen the effect of CSR on financial performance (ROA) and independent board of commissioners is not able to strengthen the effect of CSR on financial performance (ROA), the size of the board of commissioners and independent board of commissioners is not able to moderate the effect of CSR on financial performance (ROE).